Routes, trails and tracks: Trail breaking among the Inuit of Igloolik - Aporta, Claudio (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2004)
AbstractDespite significant social, economic, and technological changes, travelling remains a significant part of people's lives in the community of Igloolik, in the territory of Nunavut, Canada. When the snow covers the land and the sea ice, travellers start breaking trails, some of which recreate routes that have been used by generations of Inuit. These routes belong to the individual and social memory of the community, and this knowledge affords people safe and reliable travel to hunting and fishing grounds and between communities. This paper analyzes the characteristics of routes traditionally used by the people of Igloolik and explores the differences between land routes and sea-ice routes, the role of the trail breaker, and the characteristics of oral descriptions of routes. Finally, it addresses the issue of how the perception of trails is changing due to generational differences and the use of new transportation technologies. The study of trails and routes reveals some significant features of the Inuit understanding of the Arctic environment, provides an indication of the history of land and sea use in the area, and shows how verbal descriptions of the territory in particular and oral knowledge in general may remain unchanged or with little variation through time.